2012
DOI: 10.1029/2012gl051736
|View full text |Cite
|
Sign up to set email alerts
|

Relating global precipitation to atmospheric fronts

Abstract: [1] Atmospheric fronts are important for the day-to-day variability of weather in the midlatitudes, particularly during winter when extratropical storm-tracks are at their maximum intensity. Fronts are often associated with heavy rain, and strongly affect the local space-time distribution of rainfall. A recently developed objective front identification method that distinguishes between cold, warm and quasi-stationary fronts, is applied to reanalysis data and combined with a daily global gridded data set to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
220
1
2

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 227 publications
(248 citation statements)
references
References 19 publications
16
220
1
2
Order By: Relevance
“…Bolvin et al 2009;McPhee and Margulis 2005;Nicholson et al 2003). The precipitation data have been interpolated to the same 2.5° grid as the front data in order to facilitate the linking of the two datasets as in Catto et al (2012a).…”
Section: Reanalysis Datamentioning
confidence: 99%
See 3 more Smart Citations
“…Bolvin et al 2009;McPhee and Margulis 2005;Nicholson et al 2003). The precipitation data have been interpolated to the same 2.5° grid as the front data in order to facilitate the linking of the two datasets as in Catto et al (2012a).…”
Section: Reanalysis Datamentioning
confidence: 99%
“…Over the mid-latitude storm track regions, Catto et al (2012a) found up to 90 per cent of annual precipitation was associated with atmospheric fronts. These frontal precipitation events can cause severe flooding in the regions over which they pass (Mills et al 1995, Pitt 2008, Lavers et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Satellite observations that are dependent on atmospheric conditions also have the potential for fair-weather bias (Andersson et al, 2011). For example, the weather in the mid-to high-latitudes is dominated by atmospheric fronts with periods of high precipitation occurring with high wind speeds (Catto et al, 2012). These effects will be screened out by the satellite data and may lead to a fair-weather bias in the satellite-based datasets.…”
Section: Fair-weather Biasmentioning
confidence: 99%